21.1k views
2 votes
G(x) = f(x+1) using f(x)= x to the power of 2

User Gnowoel
by
4.8k points

1 Answer

6 votes

Answer:

g(x) = x² + 2x + 1

General Formulas and Concepts:

Algebra I

Terms/Coefficients

  • Expanding

Functions

  • Function Notation

Explanation:

Step 1: Define

Identify

g(x) = f(x + 1)

f(x) = x²

Step 2: Find

  1. Substitute in x [Function f(x)]: f(x + 1) = (x + 1)²
  2. Expand: f(x + 1) = x² + 2x + 1
  3. Redefine: g(x) = x² + 2x + 1
User Yaroslav Halchenko
by
5.5k points